FUS Recognizes G Quadruplex Structures Within Neuronal mRNAs - Imperatore, Joshua A.; McAninch, Damian S.; Valdez-Sinon, Arielle N.; Bassell, Gary J.; Mihailescu, Mihaela Rita (Frontiers in Molecular Biosciences, 2020)
Fused in sarcoma (FUS), identified as the heterogeneous nuclear ribonuclear protein P2, is expressed in neuronal and non-neuronal tissue, and among other functions, has been implicated in messenger RNA (mRNA) transport and possibly local translation regulation. Although FUS is mainly localized to the nucleus, in the neurons FUS has also been shown to localize to the post-synaptic density, as well as to the pre-synapse. Additionally, the FUS deletion in cultured hippocampal cells results in abnormal spine and dendrite morphology. Thus, FUS may play a role in synaptic function regulation, mRNA localization, and local translation. Many dendritic mRNAs have been shown to form G quadruplex structures in their 3′-untranslated region (3′-UTR). Since FUS contains three arginine-glycine-glycine (RGG) boxes, an RNA binding domain shown to bind with high affinity and specificity to RNA G quadruplex structures, in this study we hypothesized that FUS recognizes these structural elements in its neuronal mRNA targets. Two neuronal mRNAs found in the pre- and post-synapse are the post-synaptic density protein 95 (PSD-95) and Shank1 mRNAs, which encode for proteins involved in synaptic plasticity, maintenance, and function. These mRNAs have been shown to form 3′-UTR G quadruplex structures and were also enriched in FUS hydrogels. In this study, we used native gel electrophoresis and steady-state fluorescence spectroscopy to demonstrate specific nanomolar binding of the FUS C-terminal RGG box and of full-length FUS to the RNA G quadruplex structures formed in the 3′-UTR of PSD-95 and Shank1a mRNAs. These results point toward a novel mechanism by which FUS targets neuronal mRNA and given that these PSD-95 and Shank1 3′-UTR G quadruplex structures are also targeted by the fragile X mental retardation protein (FMRP), they raise the possibility that FUS and FMRP might work together to regulate the translation of these neuronal mRNA targets.